Programming : principles and practice using c++ - Stroustrup, Bjarne, ....- (Hoboken : Addison-Wesley, 2024)
Programming, Third Edition, assumes that you aim eventually to write non-trivial programs, whether for work in software development or in some other technical field. The book explains fundamental concepts and techniques in greater depth than traditional introductions. This approach will give you a solid foundation for writing useful, correct, maintainable, and efficient code. The book is an introduction to programming in general, including object-oriented programming and generic programming. It is also a solid introduction to the C++ programming language, one of the most widely used languages for real-world software. The book presents modern C++ programming techniques from the start, introducing the C++ standard library and C++11 and C++14 features to simplify programming tasks. The book is primarily designed for people who have never programmed before and has been tested with many thousands of first-year university students. It has also been extensively used for self-study. Practitioners and advanced students have also gained new insight and guidance by seeing how a master approaches the elements of his art